(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article examines the use of mobile applications and devices in monitoring physical activity, focusing on their role in promoting health and fitness. With advancements in technology, mobile apps, wearables, and smart devices have become essential tools for tracking physical activities such as steps, heart rate, calories burned, and sleep patterns. The article discusses how these technologies offer users personalized insights and real-time feedback to improve their exercise routines and overall well-being. It also explores the benefits and limitations of these technologies in the context of health promotion, physical education, and individual fitness goals.